When to use stress echocardiography in the evaluation of patients with valvular heart disease - Nkomo, Vuyisile T.; Pellikka, Patricia A.; Enriquez-Sarano, Maurice; McCully, Robert B. (SA Heart Journal, 2017)
Stress testing and stress echocardiography are firmly established diagnostic tests in the evaluation of patients with suspected or known coronary artery disease, but less established in the evaluation of patients with valvular heart disease. However, there is emerging data supporting the incremental benefit of stress testing and stress echocardiography in patients with known valvular heart disease. Particular applications include hemodynamic assessment of valve function and pulmonary response during exercise induced or chemically-induced stress to correlate with the patient’s exertional symptoms. In addition, stress testing affords the opportunity for functional assessment of ventricular systolic function for prognostication and planning for surgery.